4.1 Il realismo strategico nel governo d'impresa - Cristiano, Ciappei (Firenze University Press, 2006)
Like all the books in this series, this volume proposes wide-ranging reflections and cultural considerations pertinent to business management. Traditionally, realism is identified with a disenchanted approach to reality which is counterpoised to all forms of ideology or utopia. What is proposed here is a strategic realism which supports a humanist approach to enterprise, while steering clear of both cynicism and idealism. Seen from this angle, the crucial aspects of strategy are: the opportune selection of attainable advantages; interest as the spur to change; stratagem as a lever on the trend of events; the plan which traces the route of the opportunities called up, and the action that harvests the fruits.